82.12.8 problem Ex. 8

Internal problem ID [18773]
Book : Introductory Course On Differential Equations by Daniel A Murray. Longmans Green and Co. NY. 1924
Section : Chapter II. Equations of the first order and of the first degree. Examples on chapter II at page 29
Problem number : Ex. 8
Date solved : Tuesday, January 28, 2025 at 12:16:40 PM
CAS classification : [[_homogeneous, `class C`], _exact, _rational, [_Abel, `2nd type`, `class A`]]

\begin{align*} 2 x -y+1+\left (2 y-x -1\right ) y^{\prime }&=0 \end{align*}

Solution by Maple

Time used: 0.792 (sec). Leaf size: 33

dsolve((2*x-y(x)+1)+(2*y(x)-x-1)*diff(y(x),x)=0,y(x), singsol=all)
 
\[ y \left (x \right ) = \frac {-\sqrt {4-27 \left (x +\frac {1}{3}\right )^{2} c_{1}^{2}}+\left (3 x +3\right ) c_{1}}{6 c_{1}} \]

Solution by Mathematica

Time used: 0.122 (sec). Leaf size: 67

DSolve[(2*x-y[x]+1)+(2*y[x]-x-1)*D[y[x],x]==0,y[x],x,IncludeSingularSolutions -> True]
 
\begin{align*} y(x)\to \frac {1}{2} \left (-i \sqrt {3 x^2+2 x-1-4 c_1}+x+1\right ) \\ y(x)\to \frac {1}{2} \left (i \sqrt {3 x^2+2 x-1-4 c_1}+x+1\right ) \\ \end{align*}